On the electric field components in the collisionless plasmoid instability. (15th February 2022) - Shahraki Pour, M.; Hosseinpour, M.
Abstract : Using two-dimensional particle-in-cell simulations of collsionless plasmoid instability, the spatial and temporal variations of electric field components are investigated. The initial magnetic field is a Harris sheet which is added by a non-uniform perpendicular magnetic field (guide field). The effects of weak and medium guide field on the evolution of plasmoid instability and associated electric field are discussed with the input parameters of the solar corona with the condition ω _pe/ω _ce>1 . As the current sheet elongates, magnetic reconnection in an X-point transits into the plasmoid instability, in which secondary X-points are formed and the consequent magnetic islands coalesce and form larger islands. During the instability, electric field components show two types of disturbances. (1) Transient waves, being excited very early, propagate mainly perpendicular to the current sheet and become damped as the instability proceeds to the nonlinear stage. Fourier analysis reveals that electromagnetic right- and left-hand polarized modes parallel to the initial magnetic field and also the extraordinary mode perpendicular to the current sheet are excited. Additionally, electron Langmuir and slow magnetosonic waves are observed in both directions. (2) Inside the current sheet, an electric field is generated by the plasmoid-dominated reconnection and grows in amplitude as the plasmoid instability proceeds. Moreover, in our study, the effects of amplitude-varying guide field on the spatial structure of electric field components outside and inside the current sheet are discussed. This study is valuable because understanding the spatial and temporal variation of the electric field is an essential prerequisite for the issue of particle acceleration in plasmoid-dominated magnetic reconnection.